2005
DOI: 10.1172/jci24059
|View full text |Cite
|
Sign up to set email alerts
|

Complete rescue of obesity, diabetes, and infertility in db/db mice by neuron-specific LEPR-B transgenes

Abstract: We have generated mice that carry a neuron-specific leptin receptor (LEPR) transgene whose expression is driven by the rat synapsin I promoter synapsin-LEPR B (SYN-LEPR-B). We have also generated mice that are compound hemizygotes for the transgenes SYN-LEPR-B and neuron-specific enolase-LEPR B (NSE-LEPR-B). We observed a degree of correction in db/db mice that are hemizygous (Syn db/db) and homozygous (Syn/Syn db/db) for the SYN-LEPR-B transgene similar to that previously reported for the NSE-LEPR-B transgene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
267
0
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(281 citation statements)
references
References 39 publications
7
267
0
7
Order By: Relevance
“…LR is also expressed in gonads (47), but most of leptin's effects on the reproductive axis are relayed by the brain (48)(49)(50). One potential candidate is the AgRP neuronal population, due to its role in leptin's function and the disrupted expression of AgRP mRNA and peptide of LR Δα mice (51-53).…”
Section: Discussionmentioning
confidence: 99%
“…LR is also expressed in gonads (47), but most of leptin's effects on the reproductive axis are relayed by the brain (48)(49)(50). One potential candidate is the AgRP neuronal population, due to its role in leptin's function and the disrupted expression of AgRP mRNA and peptide of LR Δα mice (51-53).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, mice with neuronal ObR knockout show prominent obesity with gains in weight and fat. This is observed in knockout mice generated by neuronal excision of either the entire ObR with a floxed ObR line flanking exon 1 of the gene (4) or the cytoplasmic signaling tails of ObR with a floxed ObR line flanking exon 17, resulting in a mutant but membrane-bound receptor (5,15). Nonetheless, a small number of neural progenitor cells also use the GFAP promoter, and there can be variability in the efficiency and regional difference of expression (2).…”
Section: Discussionmentioning
confidence: 99%
“…They have hyperleptinemia, hyperinsulinemia, hypercorticosteronemia, infertility, and cold intolerance. Neuronal-specific mutation of ObR impairs hypothalamic functions and mimics the obese phenotype observed in db/db mice (4,5,15). The metabolic phenotype of astrocytic ObR mutation, however, has not yet been reported.…”
mentioning
confidence: 99%
“…However, in vivo studies have shown that leptin improves insulin sensitivity (Ebihara et al, 2001;Lin et al, 2002;Ogawa et al, 1999;Yamauchi et al, 2001) and normalize glucose metabolism in rodents (Chinookoswong et al, 1999;Masuzaki et al, 1999). Transgenic expression of neuron-specific leptin receptor in receptor-deficient mice leads to amelioration of diabetes (de Luca et al, 2005). Additionally, leptin has been shown to have an antidiabetic function through control of intracellular fatty acid metabolism, maintenance of glucose sensitivity, and prevention of islet lipotoxicity (Shimabukuro et al, 1997;Shimokawa and Higami, 2001;Unger, 2005).…”
Section: Discussionmentioning
confidence: 99%